Haantjes Structures for the Jacobi-Calogero Model and the Benenti Systems - Tondo, G.; Tempesta, P. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
In the context of the theory of symplectic-Haantjes manifolds, we construct the Haantjes structures of generalized Stäckel systems and, as a particular case, of the quasi-bi-Hamiltonian systems. As an application, we recover the Haantjes manifolds for the rational Calogero model with three particles and for the Benenti systems.